30 years of the quantum cascade laser - Giacomo Scalari; Jérôme Faist (Communications Physics)
It was January 1994, when the first quantum cascade laser (QCL) displayed laser action in Bell Laboratories. During these 30 years the QCL evolved incessantly, from a lab curiosity to the main on-chip source of coherent radiation in the Mid-IR and THz ranges. The journey has seen an impressive development of the QCL in several fields of laser physics and its applications, with a steady growth of research groups and companies worldwide.